2012
DOI: 10.1371/journal.pone.0041772
|View full text |Cite
|
Sign up to set email alerts
|

ExoU Activates NF-κB and Increases IL-8/KC Secretion during Pseudomonas aeruginosa Infection

Abstract: ExoU, a Pseudomonas aeruginosa cytotoxin injected into host cytosol by type III secretion system, exhibits a potent proinflammatory activity that leads to a marked recruitment of neutrophils to infected tissues. To evaluate the mechanisms that account for neutrophil infiltration, we investigated the effect of ExoU on IL-8 secretion and NF-κB activation. We demonstrate that ExoU increases IL-8 mRNA and protein levels in P. aeruginosa-infected epithelial and endothelial cell lines. Also, ExoU induces the nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…While its frequency and persistence within the lungs of cystic fibrosis (CF) patients have been the focus of a substantial amount of research effort, its virulence has also been linked to other non-CF disease states or conditions such as burns (15), wound infections (16), and nosocomial pneumonia (17). The pathogenic versatility of P. aeruginosa can be attributed to the myriad of virulence factors that it is capable of producing, including multiple toxins (18,19), degradative enzymes (20), a functional type III secretion system (21), and several different polysaccharides (22)(23)(24), each of which have been demonstrated to protect this pathogen in various stages of its life cycle. Also included in that list of important virulence factors is the extensive iron acquisition system encoded within the genome of P. aeruginosa strains.…”
Section: A S the Incidence Of Infections With Multidrug-resistant (Mdr)mentioning
confidence: 99%
“…While its frequency and persistence within the lungs of cystic fibrosis (CF) patients have been the focus of a substantial amount of research effort, its virulence has also been linked to other non-CF disease states or conditions such as burns (15), wound infections (16), and nosocomial pneumonia (17). The pathogenic versatility of P. aeruginosa can be attributed to the myriad of virulence factors that it is capable of producing, including multiple toxins (18,19), degradative enzymes (20), a functional type III secretion system (21), and several different polysaccharides (22)(23)(24), each of which have been demonstrated to protect this pathogen in various stages of its life cycle. Also included in that list of important virulence factors is the extensive iron acquisition system encoded within the genome of P. aeruginosa strains.…”
Section: A S the Incidence Of Infections With Multidrug-resistant (Mdr)mentioning
confidence: 99%
“…ExoU contributes to promote the host inflammatory response and oxidative stress through different mechanisms (151,(155)(156)(157)(158). ExoU releases arachidonic acid from cell membranes, leading to a subsequent increase in eicosanoid production by endothelial cells and airway epithelial cells (156).…”
Section: And Pi 45-biphosphate [Pi(45)p 2 ] (141)mentioning
confidence: 99%
“…ExoU inhibits caspase-1 activation and thereby the secretion of interleukin-1␤ and interleukin-18 (151). ExoU induces NF-B activation through the canonical pathway by platelet activating factor (PAF) receptor signaling, leading to IL-8 production and neutrophil recruitment (158). The ExoU-mediated activation of NF-B in turn favors PAF receptor expression, which amplifies its effects (159).…”
Section: And Pi 45-biphosphate [Pi(45)p 2 ] (141)mentioning
confidence: 99%
“…Many studies revealed that IL-8/CXCL8 expression is regulated by activation of several transcription factors, including NF-kB and C/EBPb (14,29). Our previous studies showed that NF-kB activation plays a role in thrombin-induced IL-8/CXCL8 expression (12,13).…”
Section: Involvement Of C/ebpb In Thrombin-induced Il-8/cxcl8 Expressmentioning
confidence: 99%